Sobremesa : tasty Mexican recipes for every day - Villasuso, Susana (Interlink Books, an imprint of Interlink Publishing Group, Inc., 2024)
"Sobremesa means "relaxing at the table after a heavy meal," usually after getting together with family and friends. Mexican-born chef and recipe developer Susana Villasuso is on a mission to bring the flavors of Mexico to your table, and share her culture with the world. Inspired by the dishes she learned to cook from her mother and grandmother, this debut cookbook brings together authentic, modern, simple, and tasty recipes for feeding the whole family and for all occasions, made with everyday supermarket ingredients. It's a real taste of Mexico, with a modern twist. Try some of Susana's family classics, such as: Crispy bean and ricotta taquitos with crema verde, Brown miso and porter carnitas, Salmon Ceviche with yellow beets and lime marinade, Mexican blood orange vanilla cake, and more. Discover the Mexican art of easy everyday celebrations with Sobremesa."--